2005
DOI: 10.2111/1551-5028(2005)58[256:ioaafg]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Inference of Animal Activity From GPS Collar Data on Free-Ranging Cattle

Abstract: Global positioning systems (GPSs) enable continuous and automatic tracking of an animal's position. The value of such spatialtemporal information can be improved if the corresponding activity of the animal is known. We evaluated the potential of Lotek GPS collars to predict activity of beef cattle on extensive rangeland in 2 contrasting foraging environments. Collars were configured to record animal location at intervals of 20 minutes (United States) or 5 minutes (Israel), together with counts from 2 motion se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
158
3
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(175 citation statements)
references
References 20 publications
4
158
3
10
Order By: Relevance
“…On the other hand, long distances between successive records indicate directional movement not related to grazing. Although Ungar et al (2005) concluded that distance alone is a poor predictor of cattle activity, Putfarken et al (2008) classified activities as grazing if distances between fixes at 5-minute intervals were between 6 and 100 m, and obtained 94.3 and 89.4 correct classification rates for cattle and sheep.…”
Section: Animal Behavior Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, long distances between successive records indicate directional movement not related to grazing. Although Ungar et al (2005) concluded that distance alone is a poor predictor of cattle activity, Putfarken et al (2008) classified activities as grazing if distances between fixes at 5-minute intervals were between 6 and 100 m, and obtained 94.3 and 89.4 correct classification rates for cattle and sheep.…”
Section: Animal Behavior Sensorsmentioning
confidence: 99%
“…Buerkert & Schlecht (2009) found significant differences in accuracy and precision among different units, particularly in rugged terrain. Ungar et al (2005) found that most grazing activity could be identified with models developed, but frequently other activities were classified as grazing. Overall misclassification rates were 12-14% for all activities.…”
Section: Animal Behavior Sensorsmentioning
confidence: 99%
“…Only GPS positions classified as foraging were used in this study. We interpreted consecutive animal locations at 5 m as resting and those at !100 m as long distance walking (Ungar et al 2005). The subset of consecutive animal locations that were between .5 and ,100 m were assumed to include foraging and short distance walking activities.…”
Section: Foraging Distributionmentioning
confidence: 99%
“…The study of landscape use by animals requires a record of the location of individuals over time (Ungar et al 2005). Technical and logistic difficulties in obtaining and collating such data have hampered the study of free-ranging animals in a spatially explicit way (Coughenour 1991).…”
Section: Gps Cow Collarsmentioning
confidence: 99%
“…Technical and logistic difficulties in obtaining and collating such data have hampered the study of free-ranging animals in a spatially explicit way (Coughenour 1991). Tracking animals using GPS represents a major advance in spatiotemporal data acquisition (Ungar et al 2005). Over the last decade, many species of terrestrial wildlife have successfully been fitted with GPS collars (Figure 1.1).…”
Section: Gps Cow Collarsmentioning
confidence: 99%